2013
DOI: 10.1177/0897190013507081
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ Roles in Post-September 11th Disasters

Abstract: Data suggest that pharmacists may be prepared to respond to hurricanes and biological and chemical disasters in pharmaceutical supply and patient management roles. Future research should highlight efforts to prepare health systems for the effects of nuclear, radiological, and chemical disasters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Eight articles ( Alkhalili et al, 2017 , Austin et al, 2007 , Chin et al, 2004 , Ford et al, 2013 , Ford et al, 2014 , Jiménez-Mangual et al, 2019 , Watson et al, 2019a ,b) addressed the role of pharmacists during the disaster response phase.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight articles ( Alkhalili et al, 2017 , Austin et al, 2007 , Chin et al, 2004 , Ford et al, 2013 , Ford et al, 2014 , Jiménez-Mangual et al, 2019 , Watson et al, 2019a ,b) addressed the role of pharmacists during the disaster response phase.…”
Section: Resultsmentioning
confidence: 99%
“… Ford et al (2014) reported a decreasing trend in all journals in terms of weighted counts of patient management, followed by pharmaceutical supply pharmacist role reports and policy coordination categories. Weighted counts were analyzed using chi-square goodness-of-fit analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2001, following the terrorist attacks and anthrax scares in the United States, pharmacists were identified as being invaluable during bioterrorism threats in providing their expertise (screening and treating). 3-11…”
mentioning
confidence: 99%